Branding the city of Šibenik as a sustainable tourist destination using social networks (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
Sustainable tourism, as a fast-growing cultural and economic activity, offers great opportunities for steady development of branded regions and cities. Branding is an integral part of marketing, aimed at raising awareness and creating loyalty among customers. Recent trends show the growing impact of social networks in brand creation. Croatia has one of the shortest tourist seasons in Europe, which affects the sustainability of tourism. Therefore, a pilot study of the Dalmatian town of Šibenik has been made in order to examine whether there is room for development of a sustainable tourism model through strengthening its brand with the help of modern technology, predominantly the social networks. The rich tourism potential of Šibenik has not been sufficiently exploited for sustainable tourism through a recognizable tourism brand, and the official development strategies neglected to examine the use of social networks in achieving both goals. Therefore, an online survey has been conducted in order to determine whether Šibenik is recognized as a tourist destination through social networks. The results should help in developing a systematic approach to the branding of Šibenik. It should simultaneously address the issue of its seasonal attractiveness to tourists, thus contributing to the extension of the season and increasing sustainability of tourism activities. In that way, the branding of the city will not turn into a traditional marketing strategy to promote its market, and may contribute to its sustainable development as well as serve as a model to similar cities. Keywords: Branding of Šibenik, tourist destinations, social networks, sustainable development, social marketing strategy